Belief in the Claim of an Argument Increases Perceived Argument Soundness. Issue 8 (17th November 2017) - Wolfe, Michael B.; Kurby, Christopher A.
Abstract : We examined subjects' ability to judge the soundness of informal arguments. The argument claims matched or did not match subject beliefs. In all experiments subjects indicated beliefs about spanking and television violence in a prescreening. Subjects read one-sentence arguments consisting of a claim followed by a reason and then judged the soundness of the argument. Signal detection theory analyses were used to examine discrimination performance and response bias. In Experiment 1 discrimination was not predicted by beliefs, but subjects were biased in favor of rejecting arguments as unsound when the claim was inconsistent with their beliefs compared with when it was consistent. In Experiments 2 and 3 we replicated these effects and examined neutral subjects and reasoning ability as factors. The results suggest that belief or disbelief in an argument claim biases students' judgments of the argument's soundness.